Effect of Nanoclay, Cloisite15A on the Mechanical Properties and Thermal Behavior of Glass Fiber Reinforced Polyester. (2016) - Binu, P.P.; George, K.E.; Vinodkumar, M.N.
Abstract: A series of glass fiber reinforced polyester nanocomposites have been prepared with varying compositions viz., 0, 0.5, 1, 1.5 and 2 wt % Cloisite15A as nanofiller.. The effects of nanoclay content on the mechanical, dynamic mechanical and thermal properties of nanocomposites were studied. Tensile testing, Impact testing, Dynamic Mechanical Analysis and Thermogravimetric analysis are employed to investigate mechanical and thermal characteristics. Tensile and impact test results are pointing to the optimum percentage of clay loading as 1%. Also the Tensile modulus attains the optimum status at 1% filled samples for different Cross head speed (CHS). Dynamic mechanical behavior does not indicate any consistent behavior. However the storage modulus showed an improved performance for 1% nano filled sample. The glass Transition Temperature, Tg falls in the range 95 to 110 o C for all samples. Thermogravimetric Analysis indicates the first phase of degradation starts around 200 o C for all samples. The fractured surface analyzed by Scanning Electron Microscopy(SEM) indicate brittle nature of fracture for pure polyester reinforced with glass fiber mat, Whereas the fracture changed to ductile nature by the addition of nano clay.